Histoire de l'analyse diophantienne classique : D'Abū Kāmil à Fermat - Rāshid, Rushdī (Scientia Graeco-Arabica, 2013)
This is the first study of the history of Diophantine analysis and the theory of numbers from Ab? K?mil to Fermat (9th-17th century). It thus offers an elaborate and detailed overview on a fundamental chapter on classical mathematical thought and its relation to algebra and Diophantus' Arithmetica.